Index to periodical literature on Christ and the Gospels - Mills, Watson E. (New Testament tools and studies, 1998)
This publication updates Bruce Metzger's monumental Index to the present. In addition to all the periodicals indexed by Metzger (where these are still active), this volume updates the list with a number of newer periodicals which had not yet begun publication when Metzger compiled his work. Metzger's original citations (10.000+) are complemented by an additional 4.800+ new references, using the same basic arrangement employed by Metzger.